2021
DOI: 10.1038/s41598-021-99877-7
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus availability and leaching losses in annual and perennial cropping systems in an upper US Midwest landscape

Abstract: Excessive phosphorus (P) applications to croplands can contribute to eutrophication of surface waters through surface runoff and subsurface (leaching) losses. We analyzed leaching losses of total dissolved P (TDP) from no-till corn, hybrid poplar (Populus nigra X P. maximowiczii), switchgrass (Panicum virgatum), miscanthus (Miscanthus giganteus), native grasses, and restored prairie, all planted in 2008 on former cropland in Michigan, USA. All crops except corn (13 kg P ha−1 year−1) were grown without P fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 65 publications
3
12
0
Order By: Relevance
“…P leaching losses (kg P ha −1 ), which were previously reported by Hussain et al (2021), were calculated by multiplying the total dissolved P concentration (mg L −1 ) in the soil leachates by daily drainage (percolation) rates (m 3 ha −1 ) estimated with the Systems Approach for Land Use Sustainability (SALUS) crop growth model (Basso & Ritchie, 2015). The SALUS water balance sub-model simulates daily surface runoff, saturated and unsaturated water flow, drainage, root water uptake, and evapotranspiration during growing and non-growing seasons and has been well calibrated for KBS soil and climatic conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P leaching losses (kg P ha −1 ), which were previously reported by Hussain et al (2021), were calculated by multiplying the total dissolved P concentration (mg L −1 ) in the soil leachates by daily drainage (percolation) rates (m 3 ha −1 ) estimated with the Systems Approach for Land Use Sustainability (SALUS) crop growth model (Basso & Ritchie, 2015). The SALUS water balance sub-model simulates daily surface runoff, saturated and unsaturated water flow, drainage, root water uptake, and evapotranspiration during growing and non-growing seasons and has been well calibrated for KBS soil and climatic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The SALUS water balance sub-model simulates daily surface runoff, saturated and unsaturated water flow, drainage, root water uptake, and evapotranspiration during growing and non-growing seasons and has been well calibrated for KBS soil and climatic conditions. The SALUS model was originally developed at KBS and has been used in studies of evapotranspiration (Hamilton, 2015;Hamilton et al, 2018;Hussain et al, 2019) and nutrient leaching (Hussain et al, 2019(Hussain et al, , 2020(Hussain et al, , 2021 from KBS soils. SALUS predictions of growingseason evapotranspiration-and hence percolation as the balance between precipitation and evapotranspirationare consistent with independent measurement based on eddy covariance (Abraha et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Perennial plants that have a higher root-to-shoot ratio (24), higher root biomass production (84-86), and higher rootassociated C input through exudation and turnover (87,88) can improve soil properties that are closely linked to soil fertility, such as soil aggregation, water-holding capacity, and microbial biomass and diversity. In addition, perennial plants are known to make better use of nitrogen, as their deeper and more extensive root systems optimize inorganic N and P retention in the soil, thus reducing leaching of these elements (81,(89)(90)(91)(92). In addition, some species contribute to N retention by translocating N in their belowground biomass, such as in rhizomes at the end of the growing season (24).…”
Section: Fertilitymentioning
confidence: 99%
“…(1997) found that nitrate‐nitrogen (NO 3 − –N) loads in subsurface drainage from continuous corn and corn–soybean systems were 37 and 35 times greater, respectively, than from perennial crops. In contrast, few studies have examined the effects of perennial crops on subsurface P loss, and the results have been inconsistent and dependent on crop type and management (Brye et al., 2002; Daigh et al., 2015; Hussain, 2021; T. Q. Zhang et al., 2015). For example, Daigh et al.…”
Section: Introductionmentioning
confidence: 99%